Handbook of Mathematical Geosciences 2018
DOI: 10.1007/978-3-319-78999-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Geosciences: Local Singularity Analysis of Nonlinear Earth Processes and Extreme Geo-Events

Abstract: In the first part of the chapter, the status of the discipline of mathematical geosciences (MG) is reviewed and a new definition of MG as an interdisciplinary field of science is suggested. Similar to other disciplines such as geochemistry and geophysics, mathematical geosciences or geomathematics is the science of studying mathematical properties and processes of the Earth (and other planets) with prediction of its resources and changing environments. In the second part of the chapter, original research resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Fractals can be considered geometries with fractal dimensions (e.g., noninteger) that no longer possess the Lebesgue additive property [26]. Accordingly, the ordinary integral and derivative operations no longer apply to the fractal geometry with singularity [25]. Before introducing an extension of classical calculus to fractal calculus, there is a need to briefly introduce the common notions used for the representation of the Lebesgue integral and derivative operations and FC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fractals can be considered geometries with fractal dimensions (e.g., noninteger) that no longer possess the Lebesgue additive property [26]. Accordingly, the ordinary integral and derivative operations no longer apply to the fractal geometry with singularity [25]. Before introducing an extension of classical calculus to fractal calculus, there is a need to briefly introduce the common notions used for the representation of the Lebesgue integral and derivative operations and FC.…”
Section: Methodsmentioning
confidence: 99%
“…Studies also indicated that earthquakes with magnitudes greater than 5.0 worldwide recorded from January 1991 to 31 December 1996 are generally shallow, with depths less than 70 km [17]. The author's earlier research on the distribution of earthquakes along the subduction zones of Pacific plates indicated that earthquakes are clustered around 34-44 km, and the depth distribution of earthquakes can be described by power law function with singularity [25]. There is a lack of systemic and comparative studies about the nonlinear decay of clusters of earthquakes around the Moho and their associations with global plate tectonics.…”
Section: Frequency-depth Clusters Of Earthquakes At the Converging Pl...mentioning
confidence: 98%
See 1 more Smart Citation
“…The local singularity analysis have been successfully utilized to explore complex and nonlinear extreme geological events and geological processes, especially in the field of geochemistry [20,21]. For instance, local singularity analysis method has been applied to the analysis of global zircon U-Pb ages which uncovers the evolutionary process of the continental crust [18].…”
Section: Introductionmentioning
confidence: 99%